الاعتراضات الغربیۃ علیٰ الحضارۃ الاسلامیۃ والجھود العلمیۃ والفکریۃ للمفکرین المسلمین فی ردھا: دراسۃ نقدیۃ وتحلیلیۃ: Western Objections to Islamic Civilization and the Scholarly Efferts and Responses" of Muslim Intellectuals: A Critical and Analytical Study (Al-Aasar, 2025)
Since the dawn of Islam, non-Muslim thinkers have attempted to disillusion people from the religion of Islam and Islamic sciences by voicing objections and doubts about the Quran, Hadith and the life of the Prophet Muhammaad ﷺ, Islamic jurisprudence and law, and Islamic history to serve their own purposes. The Westerners first shattered the unity of Muslims by dividing them into fragments and transforming the Islamic state into smaller states, then promoting regional languages to distance them from the Arabic language. Western thinkers, particularly Orientalists, studied Islamic history and distorted it before sending it back to Muslim countries, aiming to demoralize Muslims and negatively portray Islamic history to disillusion the new generation about Islam, so that Muslims become suspicious of their history and lose the courage to progress. According to Western thinkers, Islamic law is an outdated and obsolete system that requires reform, and without such reforms, this system cannot effectively be implemented and enforced in society. They have targeted Islamic jurisprudence and the legal system, deeming the punitive system of Islam as unjust and oppressive, and have characterized the arrival of Islam in the Indian subcontinent and the conquests and governance of Muslim conquerors as tyranny, oppression, and plunder. This was a period that was no less than a trial for Muslims in the subcontinent, and these were all the challenges that Muslim scholars, thinkers, and intellectuals had to face: on one hand, answering the objections and doubts of the West and Orientalists, and on the other hand, presenting the true concept of Islam and an accurate depiction of Islamic history and culture in order to establish the Qur'anic commandments, while removing doubts and ambiguities from the hearts and minds of the Muslims of the subcontinent and awakening the true Islamic spirit, which was essentially the real achievement of the reformers of Islam. For this purpose, Allah Almighty raised such Muslim scholars, reformers, and thinkers in the Indian subcontinent who not only refuted those Western doubts and objections with arguments but also provided philosophical answers, thus saving the Muslims of the subcontinent from the trials of skepticism and ambiguity and opposing this atheistic philosophy of Westernism.